(untitled) (Damascus University Journal for legal sciences, 2024)
Islamic law is characterized as being valid for every time and place, capable of accommodating contemporary issues, in a way that ensures that the questioner can find his answer in them after referring to the people of the fatwa scholars. Through their reliance on the original evidence and accessory. Among them, Ibn Abidin, who was concerned with setting the rules that the mufti would follow when there were multiple ijtihad statement And he clarified the ruling on issues emerging in his time, and this is what was included in his well-known hashiatuh (footnote) "Rad Al-Muhtar’s on Al-Durr al-Mukhtar". This research came out with an independent study of the most important developments related to issues and incidents of fatwa according to Ibn Abdeen. Through his Hashiatuh that mentioned With what he answered in the issues of marriage and divorce, and then studying them as a jurisprudential study compared to the Syrian law, To clarify the methodological vision of Ibn Abidin in dealing with these facts, and evidence inferred in each issue.